Performance evaluation of the FAST™ System and the FAST-PBC Prep™ cartridges for speeded-up positive blood culture testing - Verroken, Alexia; Hajji, Chaima; Bressant, Florian; Couvreur, Jonathan; Anantharajah, Ahalieyah; Rodriguez-Villalobos, Hector (Frontiers in Microbiology, 2022)
Objectives: As time to appropriate antimicrobial therapy is major to reduce sepsis mortality, there is great interest in the development of tools for direct identification (ID) and antimicrobial susceptibility testing (AST) of positive blood cultures (PBC). Very recently, the FAST System (Qvella) has been developed to isolate and concentrate microorganisms directly from PBCs, resulting in the recovery of a Liquid Colony (LC) within 30 minutes. The LC can be used as equivalent of an overnight subcultured colony for downstream testing. We aimed to evaluate the performances of the FAST System and FAST-PBC Prep cartridges by testing the resulting LC for direct ID, AST and rapid resistance detection. Methods: Prospectively, FAST System testing was carried out on each patient’s first PBC with a monomicrobial Gram-stain result. In the second arm of the study, FAST System testing was carried out on blood cultures spiked with multidrug-resistant bacteria. Downstream testing using the LC included MALDI-TOF MS ID with the Bruker Biotyper smart system, rapid resistance detection testing including the Abbott Diagnostics Clearview PBP2a SA Culture Colony Test (PBP2a) and the Bio-Rad LACTA Test (LT). AST was performed using the Becton Dickinson Phoenix System or by Bio-Rad disk diffusion using filter paper disk following EUCAST 2020 breakpoint criteria. Results: FAST System testing was completed on 198 prospective PBCs and 80 spiked blood cultures. After exclusion of polymicrobial blood cultures, performance evaluation compared with standard of care results was carried out on 266 PBCs. Concordant, erroneous and no ID results included 238/266 (89.5%), 1/266 (0.4%), 27/266 (10.2%) PBCs, respectively. Sensitivity and specificity for PBP2a were 100% (10/10) and 75% (15/20), respectively. Sensitivity and specificity for LT were 95.8% (23/24) and 100% (42/42), respectively. Categorical agreement for all 160 tested strains was 98% (2299/2346) with 1.2% (8/657) very major errors and 0.7% (10/1347) major errors. Conclusion: FAST System testing is a reliable approach for direct downstream testing of PBCs including MALDI-TOF MS ID, BD Phoenix and Bio-Rad disk diffusion AST as well as rapid resistance testing assays. Next steps include optimal integration of the FAST System in the PBC workflow with a view towards clinical studies.